Crizotinib acts as ABL1 inhibitor combining ATP-binding with allosteric inhibition and is active against native BCR-ABL1 and its resistance and compound mutants BCR-ABL1T315I and BCR-ABL1T315I-E255K - Mian, Afsar Ali (2021)
Resistance remains the major clinical challenge for the therapy of Philadelphia chromosome–positive (Ph+) leukemia. With the exception of ponatinib, all approved tyrosine kinase inhibitors (TKIs) are unable to inhibit the common “gatekeeper” mutation T315I. Here we investigated the therapeutic potential of crizotinib, a TKI approved for targeting ALK and ROS1 in non-small cell lung cancer patients, which inhibited also the ABL1 kinase in cell-free systems, for the treatment of advanced and therapy-resistant Ph+ leukemia. By inhibiting the BCR-ABL1 kinase, crizotinib efficiently suppressed growth of Ph+ cells without affecting growth of Ph− cells. It was also active in Ph+ patient-derived long-term cultures (PD-LTCs) independently of the responsiveness/resistance to other TKIs. The efficacy of crizotinib was confirmed in vivo in syngeneic mouse models of BCR-ABL1- or BCR-ABL1T315I-driven chronic myeloid leukemia–like disease and in BCR-ABL1-driven acute lymphoblastic leukemia (ALL). Although crizotinib binds to the ATP-binding site, it also allosterically affected the myristol binding pocket, the binding site of GNF2 and asciminib (former ABL001). Therefore, crizotinib has a seemingly unique double mechanism of action, on the ATP-binding site and on the myristoylation binding pocket. These findings strongly suggest the clinical evaluation of crizotinib for the treatment of advanced and therapy-resistant Ph+ leukemia.